ASSOCIATION BETWEEN SERUM VITAMIN D AND CHRONIC RHINOSINUSITIS : A SYSTEMATIC REVIEW - Agung Nugroho, Satya; Gwen Vaganesha, Nazalla; Habib Afifudin, Hasnan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Chronic rhinosinusitis is a highly heterogeneous chronic inflammation of the upper respiratory tract caused by immune dysfunction in human beings. However, the underlying etiology of this disease has not yet been well established. Several trials have revealed that serum vitamin D level abnormality might play a role in the pathophysiology of chronic rhinosinusitis. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 1.354 articles, whereas the results of our search on SagePub brought up 214 articles. The results of the search conducted for the last year of 2013 yielded a total 4 articles for PubMed and 7 articles for SagePub. In the end, we compiled a total of 6 papers, 4 of which came from PubMed and 2 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, our systematic review of 5 studies illustrates the lower serum vitamin D status in CRS patients, which indicates that people might get benefit from appropriate vitamin D supplementation. Therefore, due to the heterogeneity of the subjects, more well-designed prospective RCTs should be carried out to further validate these findings in for the general population in the future.